2021
DOI: 10.1093/cvr/cvab115
|View full text |Cite
|
Sign up to set email alerts
|

Human-induced pluripotent stem cells in cardiovascular research: current approaches in cardiac differentiation, maturation strategies, and scalable production

Abstract: Manifestations of cardiovascular diseases (CVDs) in a patient or a population differ based on inherent biological makeup, lifestyle, and exposure to environmental risk factors. These variables mean that therapeutic interventions may not provide the same benefit to every patient. In the context of CVDs, human-induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) offer an opportunity to model CVDs in a patient-specific manner. From a pharmacological perspective, iPSC-CM models can serve as go/no-go tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…Moreover, using iPSCderived cardiomyocytes (iPSC-CMs) and genome editing approaches, a wide number of monogenic and complex cardiac pathogenesis have been studied in vitro, providing newer insights into disease mechanisms. 6 Human iPSCs-CMs has also emerged as a cornerstone in drug Thomas et al Engineered Cardiovascular Models…”
mentioning
confidence: 99%
“…Moreover, using iPSCderived cardiomyocytes (iPSC-CMs) and genome editing approaches, a wide number of monogenic and complex cardiac pathogenesis have been studied in vitro, providing newer insights into disease mechanisms. 6 Human iPSCs-CMs has also emerged as a cornerstone in drug Thomas et al Engineered Cardiovascular Models…”
mentioning
confidence: 99%
“…hiPSC-CMs have emerged as a robust model for studying the molecular and cellular mechanisms of cardiac pathophysiology. 108 In a proof-of-concept study, Wnorowski et al 57 demonstrated the feasibility of long-term cell culture of hiPSC-CMs on the ISS. Specifically, monolayers of beating hiPSC-CMs from 3 individuals were plated in BioCell, a fully contained cell culture vessel, and launched to the ISS on a SpaceX Dragon spacecraft.…”
Section: Leveraging Spaceflight To Advance Cardiovascular Research On...mentioning
confidence: 99%
“…Therefore, it is essential to advance our models of cardiovascular diseases to develop better treatments for patients. Modeling cardiovascular diseases, screening for drug toxicities, and understanding heart developmental processes remain persistent challenges to the cardiovascular community due to their requirements of large quantities of well-characterized and highly uniform populations of human cardiomyocytes [42]. Although great strides have been made using animal models, there are key aspects of human cardiovascular physiology that these models fail to recapitulate.…”
Section: Significance Of Studying the Effects Of Cryopreservation On ...mentioning
confidence: 99%